#TITLE_ALTERNATIVE# - DWI SAPUTRO (NIM : 10212088), OKI
Reservoir rock characterization is very important for oil and gas exploration. It can be conduct by interpreting physical parameter from rocks such as porosity and permeability. Nowadays, Digital Rock Physics Method is used to compute permeability of real rocks using numerical simulation. In this research, Palabos software package based on Lattice Boltzmann (LBM) numerical method is used to investigate the effect of impurities on rock models permeability. Rock model with polyhedron grain is chosen. Kozeny-Carman equation & analytical formula of fluid flow in pipe are used as validation scheme. Error between Palabos & analytical formula for single pipe is about 2.06%. Comparing Palabos to Kozeny-Carman for small size (64 x 64 x 64) and medium size (150 x 150 x 150) gives difference 4.7 Darcy & 3 Darcy respectively.